Medical Referral Patterns and Etiologies for Children With Mild-to-Severe Hearing Loss. Issue 4 (July 2019) - Judge, Paul D.; Jorgensen, Erik; Lopez-Vazquez, Monica; Roush, Patricia; Page, Thomas A.; Moeller, Mary Pat; Tomblin, J. Bruce; Holte, Lenore; Buchman, Craig
Abstract : Objectives: To (1) identify the etiologies and risk factors of the patient cohort and determine the degree to which they reflected the incidence for children with hearing loss and (2) quantify practice management patterns in three catchment areas of the United States with available centers of excellence in pediatric hearing loss. Design: Medical information for 307 children with bilateral, mild-to-severe hearing loss was examined retrospectively. Children were participants in the Outcomes of Children with Hearing Loss (OCHL) study, a 5-year longitudinal study that recruited subjects at three different sites. Children aged 6 months to 7 years at time of OCHL enrollment were participants in this study. Children with cochlear implants, children with severe or profound hearing loss, and children with significant cognitive or motor delays were excluded from the OCHL study and, by extension, from this analysis. Medical information was gathered using medical records and participant intake forms, the latter reflecting a caregiver's report. A comparison group included 134 children with normal hearing. A Chi-square test on two-way tables was used to assess for differences in referral patterns by site for the children who are hard of hearing (CHH). Linear regression was performed on gestational age and birth weight as continuous variables. Risk factors were assessed using t tests. The alpha value was set at p < 0.05. Results: Neonatal intensive care unit stay, mechanical ventilation, oxygen requirement, aminoglycoside exposure, and family history were correlated with hearing loss. For this study cohort, congenital cytomegalovirus, strep positivity, bacterial meningitis, extracorporeal membrane oxygenation, and loop diuretic exposure were not associated with hearing loss. Less than 50% of children underwent imaging, although 34.2% of those scanned had abnormalities identified. No single imaging modality was preferred. Differences in referral rates were apparent for neurology, radiology, genetics, and ophthalmology. Conclusions: The OCHL cohort reflects known etiologies of CHH. Despite available guidelines, centers of excellence, and high-yield rates for imaging, the medical workup for children with hearing loss remains inconsistently implemented and widely variable. There remains limited awareness as to what constitutes appropriate medical assessment for CHH.